Thermal skin reference values in healthy late pregnancy - Simões, R (2013)
Digital thermal imaging has been employed in medicine for over 50 years. However, its use has been focused on vascular, musculoskeletal and neurological conditions, while other potential applications, such as obstetrics, have been much less explored. This paper presents a study conducted during 2011 at the Hospital of Braga on a group of healthy pregnant women in the last third of gestation. The analysis focused on characterizing typical pregnant women steady temperature profiles in specific defined regions of interest (ROI), and determining if the thermal symmetry values for late pregnant healthy women are in line with the values for non-pregnant healthy women. A temperature distribution pattern was found in the defined ROI. The obtained thermal symmetry value had a maximum of 0.3 +/- 0.2 degrees C, and there was no evidence for the influence of age (p > 0.05) in the observed group. The influence of the BMI requires further investigation since one ROI (P2 right) presented a p = 0.059, close to the threshold of statistical evidence in the influence of BMI. The study group presented symmetry values in line with non-pregnant reference values, but the profiles in temperature distribution are different. Assumptions can therefore now be used with higher confidence when assessing abnormalities in specific pathologic states during pregnancy using the defined ROI. This work represents a first contribution towards establishing guidelines for future research in this specific field of study.